Determinants of female fertility in ASEAN-5: empirical evidence from bounds cointegration test - Subramaniam, Thirunaukarasu; Loganathan, Nanthakumar; Devadason, Evelyn Shyamala (World Scientific Publishing, 2018)
The ASEAN countries have been experiencing drastic declines in fertility of more than 10 percent, particularly since the 1990s. Though the literature on fertility has clearly delineated the importance of income, female labor force participation and infant mortality as key determinants of fertility rates (FRs), the empirical findings from previous studies remains at best mixed. This study therefore identifies the determinants of female fertility for the countries, namely Indonesia, Malaysia, Philippines, Singapore and Thailand (ASEAN-5 countries), spanning the period 1980-2010. Using the Autoregressive Distributed Lag (ARDL) cointegration and causality techniques, the main findings of the study are summarized as follows: First, a long-run (LR) stable relationship is evident between female fertility, female labor force participation, income and infant mortality for ASEAN-5. Second, there is a deviation of FRs from the short-run (SR) to the LR equilibrium for ASEAN-5, with the highest and lowest speed of adjustment recorded for Malaysia and Thailand, respectively. Third, FR and economic stability are found to be complementary in the LR for ASEAN-5. When the joint LR and SR causalities are considered, we found that female labor force participation, income and infant mortality have dynamic relationships with FR for all the five ASEAN countries.